The Influence of Market Orientation on Business Performance through Social Media Network Ties Study on Halal Center Unusida MSMEs - sholikhah, afifatus; Novie, Muhafidhah; Kamila, Edita Rachma; Nugrahanti, Ratri Buda (GREENOMIKA, 2025)
This study aims to analyze the effect of Market Orientation on Business Performance through Social Media Network Ties among SMEs affiliated with the Halal Center at Nahdlatul Ulama University of Sidoarjo (UNUSIDA). A quantitative approach was employed using probability sampling with the proportionate cluster simple random sampling method. The study involved 110 SME respondents. Data were collected through a structured questionnaire and documentation, and analyzed using the Partial Least Squares (PLS) method with SmartPLS 3 software. The findings indicate that Market Orientation has a positive and significant effect on Business Performance (β = 0.47, p < 0.01) and on Social Media Network Ties (β = 0.58, p < 0.001). Furthermore, Social Media Network Ties significantly affect Business Performance (β = 0.36, p < 0.01) and partially mediate the relationship between Market Orientation and Business Performance. The coefficient of determination (R²) for Business Performance is 0.62, indicating that 62% of its variance is explained by the variables in the model. These results imply that a strong market orientation, combined with effective utilization of social media networks, enhances competitiveness and business performance among halal SMEs. Policymakers and supporting institutions should promote digital literacy and social media–based marketing strategies to strengthen the growth of Indonesia’s halal economy.